OP03 Knowledge, attitude, and experience of advance care planning among healthcare professionals in asia: a systematic review. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Rietjens, J; Martina, D; Kristanti, S; Bramer, W; Mori, M; Korfage, I; Van der Heide, A; Van der Rijt, CCD
Abstract : Background: Despite universal recognition of advance care planning's (ACP) importance, collectivism spirit in Asia may impact its uptake. Aims: To gain insight into health care professionals' (HCP) knowledge of, attitude towards, and experience with ACP in Asia. Methods: We systematically searched four electronic databases for quantitative and qualitative studies on ACP in East and South East Asian countries. Anticipating unfamiliarity with ACP, we operationalized ACP broadly, covering discussions about future medical care and documentation thereof. Results: Among 3, 358 identified studies, 41 were eligible; 36 applied quantitative and 5 applied qualitative design. Most studies were conducted in high-income countries: Japan (16), South Korea (13), Singapore (4), Hong Kong (4), and Taiwan (3). While twenty-nine studies addressed documentation of preferences, only six addressed ACP and end-of-life discussion respectively. Ten studies addressing knowledge indicated moderate awareness of ACP. Thirty studies on attitudes showed that although many HCPs considered ACP and involving patient and family in its process important, some found initiating ACP difficult. This hesitation was partly due to fear of conflicts with family members and the legal consequences. Twenty studies on experiences indicated that actual engagement of HCP in ACP is limited, too late, and mostly only involved family without patients. Conclusion: Although being considered potentially important, ACP did not occur often. HCPs seem to be reluctant to engage in ACP. The role of family in ACP is crucial in Asia. However, evidence was highly heterogeneous and limited to a few high-income countries, which limits its generalizability to other Asian countries.